2016
DOI: 10.1103/physrevb.94.085133
|View full text |Cite
|
Sign up to set email alerts
|

Quantum electrodynamical theory of high-efficiency excitation energy transfer in laser-driven nanostructure systems

Abstract: A fundamental theory is developed for describing laser-driven resonance energy transfer (RET) in dimensionally constrained nanostructureswithin the framework of quantum electrodynamics. The process of RET communicates electronic excitation between suitably disposed emitter and detector particles in close proximity, activated by the initial excitation of the emitter. Here, we demonstrate that the transfer rate can be significantly increased by propagation of an auxiliary laser beam through a pair of nanostructu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…Inter alia, the QED analysis also showed that the two supposedly different mechanisms can never compete in determining the distance-dependent dynamics of energy transfer. The results, which have now become standard textbook material in the field of nano-optics [45], have found recent applications on energy transfer in engineered nanoscale structures [149,150].…”
Section: A Differences In Perspectivementioning
confidence: 99%
“…Inter alia, the QED analysis also showed that the two supposedly different mechanisms can never compete in determining the distance-dependent dynamics of energy transfer. The results, which have now become standard textbook material in the field of nano-optics [45], have found recent applications on energy transfer in engineered nanoscale structures [149,150].…”
Section: A Differences In Perspectivementioning
confidence: 99%
“…Further examples have been explored in considering the two major relaxation routes of an electronically excited molecule: fluorescence and resonant energy transfer (RET). Application of off-resonance light to both these processes lead to increased control through laser-modified fluorescence and laser-assisted resonance energy transfer (LARET) [10][11][12][13][14][15] . In laser-assisted fluorescent emission, the forward Rayleigh scattering of the detuned laser leads to either an enhanced or suppressed rate of fluorescent emission, in an analogous fashion to the effect on absorption.…”
Section: Optical Catalysis Of Light-matter Processesmentioning
confidence: 99%
“…The minute nature of these devices theoretically enables minimally invasive treatment of cancers [46]. Therefore, various attempts are being made at understanding light, heat, and matter interactions [47], energy transportation [48][49][50][51], as well as the modeling of such nanoscopic devices targeting this application, ranging from gold nanoshells [52] to nanoscopic lasers known as spasers [53][54][55].…”
Section: B Proposed Application: Photothermal Cancer Therapymentioning
confidence: 99%